Analysis of Factors Affecting the Sleep Quality of Patients in Intensive Care Unit - Sri Suparti; Jebul Suroso; Asiandi Asiandi (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Lack of sleep in patients in the Intensive Care Unit (ICU) is associated with dysfunction of the immune, cardiovascular, metabolic, memory, and cognition systems, as well as increased mortality. Various factors that are thought to be related to patient sleep quality come from patient and environmental factors. The purpose of this study was to determine the factors that affect the sleep quality of ICU patients. This research is a quantitative study, using a cross-sectional approach, with as many as 44 patients involved in this study. The research instrument used the observation sheet and The Richards-Campbell Sleep Questionnaire (RCSQ) is also equipped with a thermohygrometer to measure temperature and humidity and a sound level meter to measure noise. Data analysis used the Spearman Rank test, and research ethics was obtained from the Ethics Commission of RSMS Margono. The results showed that most of them were women (75%), aged ≥40 years (68.2%) with the most days of stay less than 4 (93.2%), postoperative (95.5), and with poor sleep quality (72.7%). Factors that affected the sleep quality of the patient are heart rate (0.030), MAP (0.042), patient pain score (0.031), and sleep position (0.002). There was no affecting the SpO2 factor, temperature humidity, noise, patient perceptions of noise, light, and action with p value> 0.05. In conclusion, most of the respondents have poor sleep quality. There is an effect of the heart rate, sleep position, and pain score on the patient's sleep quality. It is necessary to apply a combination of pharmacological management and nursing measures to improve sleep quality.